Automatic Saving and the Rate of Accumulation - Carver, T. N. (Quarterly Journal of Economics, 1924)
Automatic Saving and the Rate of Accumulation Get access T. N. Carver T. N. Carver Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 38, Issue 2, February 1924, Pages 347–351, https://doi.org/10.2307/1884018 Published: 01 February 1924